PENGAWASAN PEMILIHAN UMUM LEGISLATIF DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU TAHUN 2014 - Andrean, Nico; Tinov, M.Y.Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Election is one of the important aspects of democration in a country, because through a general election, the implementation of sovereignty can be implemented well, yet it needs to be well planned, controlled, supervised. Related to supervision, thus formed supervisory committe of general election regulated by law no 10 year 2008 about the general election of DPD, DPR, and DPRD. The supervisory of the implementation of general election according to the law no 10 year 2008, is performed by Badan Pengawas Pemilu (Bawaslu) in the central, Supervisory Committe in province, and district, sub-district, field, and overseas. The aims of this research are to percieve and analyse the implementation of surveillance of general election by Supervisory Committe of legislative election 2014 in Marpoyan Damai sub-district, Pekanbaru. This study is expected to be used as reference material for development, improvement, and as well as performance monitoring especially for the next Supervisory Committes of general election in order to achieve desired goal and as the input to determine policies related to surveillance in the development of existing organizations. In the result of this study is found that overall implementation of legislative election 2014 in Marpoyan Damai sub-district had not been fuctioning effectively. It can be seen from the the first step of implementation of supervisory process until the last step of the implementation of the election. Technical factor such as the delay of the formation of Supervisory Committe in district, sub-district, and field in Pekanbaru, thus equipping of the duties and authority of the Supervisory Committee delayed that will result in unmonitored of 3 (three) stages of election 2014 in Pekanbaru. Administrative factor such as there was no techinal guidance and clear instruction for the Supervisory Committes, hence they did not performed well in supervising. Beside, secretariat of the Supervisory Committe who boarded the secreatiat of KPU lead to disturbance of the indepence of Supervisory Committes. Key words: supervisory, election, legislative.